2017
DOI: 10.1371/journal.pone.0177436
|View full text |Cite
|
Sign up to set email alerts
|

Economic evaluation of policy options for dialysis in end-stage renal disease patients under the universal health coverage in Indonesia

Abstract: ObjectivesThis study aims to assess the value for money and budget impact of offering hemodialysis (HD) as a first-line treatment, or the HD-first policy, and the peritoneal dialysis (PD) first policy compared to a supportive care option in patients with end-stage renal disease (ESRD) in Indonesia.MethodsA Markov model-based economic evaluation was performed using local and international data to quantify the potential costs and health-related outcomes in terms of life years (LYs) and quality-adjusted life year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
47
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(56 citation statements)
references
References 23 publications
4
47
0
3
Order By: Relevance
“…A cost‐effectiveness comparison of “HD‐first” vs “PD‐first” policy was conducted in Indonesia. The comparison revealed that an HD‐first policy would cost more than twice the cost of a PD‐first policy, but only after 5 years with quality‐adjusted life years scores favoring PD . A PD‐first policy has been advocated by some groups in the US citing similar benefits …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A cost‐effectiveness comparison of “HD‐first” vs “PD‐first” policy was conducted in Indonesia. The comparison revealed that an HD‐first policy would cost more than twice the cost of a PD‐first policy, but only after 5 years with quality‐adjusted life years scores favoring PD . A PD‐first policy has been advocated by some groups in the US citing similar benefits …”
Section: Discussionmentioning
confidence: 99%
“…The comparison revealed that an HD-first policy would cost more than twice the cost of a PD-first policy, but only after 5 years with quality-adjusted life years scores favoring PD. 34 policy has been advocated by some groups in the US citing similar benefits. 35 It has been speculated that the daunting task of learning complex technologies could be playing a factor in non-bachelor-degreed individuals from outlying boroughs.…”
Section: Discussionmentioning
confidence: 99%
“…13 The major cost of a renal transplant and dialysis was covered by Jaminan Kesehatan National (JKN), the National Health Insurance Scheme of Indonesia that is managed by the Health Social Security Institution or Badan Penyelenggara Jaminan Sosial (BPJS). 11,14 Patients on HD therapy received dialysis treatments twice in a week with 5 hours for each treatment. Meanwhile for CAPD patients, the government supported the cost of catheter insertion and dialysate for up to four times daily fluid exchange.…”
Section: Introductionmentioning
confidence: 99%
“…This cost burden caused CKD to be ranked second in Indonesian government spending for catastrophic illness. 14,15 Although renal transplantation was the best therapy for ESRD patients, limited number of kidney donors had made the patients to opt for either HD or CAPD. 12,14 It was estimated that only 53% of ESRD patients in Indonesia were on dialysis, and HD was still the most preferred option of RRT compared to CAPD.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation